Targeting fatty acid amide hydrolase and transient receptor potential vanilloid‐1 simultaneously to modulate colonic motility and visceral sensation in the mouse: A pharmacological intervention with N‐arachidonoyl‐serotonin (AA‐5‐HT). Issue 12 (11th July 2017) - Bashashati, M.; Fichna, J.; Piscitelli, F.; Capasso, R.; Izzo, A. A.; Sibaev, A.; Timmermans, J.‐P.; Cenac, N.; Vergnolle, N.; Di Marzo, V.; Storr, M.
Abstract: Background: Endocannabinoid anandamide (AEA) inhibits intestinal motility and visceral pain, but it may also be proalgesic through transient receptor potential vanilloid‐1 (TRPV1). AEA is degraded by fatty acid amide hydrolase (FAAH). This study explored whether dual inhibition of FAAH and TRPV1 reduces diarrhea and abdominal pain. Methods: Immunostaining was performed on myenteric plexus of the mouse colon. The effects of the dual FAAH/TRPV1 inhibitor AA‐5‐HT on electrically induced contractility, excitatory junction potential (EJP) and fast (f) and slow (s) inhibitory junction potentials (IJP) in the mouse colon, colonic propulsion and visceromotor response (VMR) to rectal distension were studied. The colonic levels of endocannabinoids and fatty acid amides were measured. Key Results: CB1‐positive neurons exhibited TRPV1; only some TRPV1 positive neurons did not express CB1. CB1 and FAAH did not colocalize. AA‐5‐HT (100 nM‐10 μM) decreased colonic contractility by ~60%; this effect was abolished by TRPV1 antagonist 5′‐IRTX, but not by CB1 antagonist, SR141716. AA‐5‐HT (1 μM‐10 μM) inhibited EJP by ~30% and IJPs by ~50%. The effects of AA‐5‐HT on junction potentials were reversed by SR141716 and 5`‐IRTX. AA‐5‐HT (20 mg/kg; i.p.) inhibited colonic propulsion by ~30%; SR141716 but not 5`‐IRTX reversed this effect. AA‐5‐HT decreased VMR by ~50%‐60%; these effects were not blocked by SR141716 or 5`‐IRTX. AA‐5‐HT increased AEA in the colon. Conclusions and Inferences: The effects of AA‐5‐HT on visceral sensation and colonic motility are differentially mediated by CB1, TRPV1 and non‐CB1/TRPV1 mechanisms, possibly reflecting the distinct neuromodulatory roles of endocannabinoid and endovanilloid FAAH substrates in the mouse intestine. Abstract : AA‐5‐HT a dual FAAH inhibitor and TRPV1 antagonist modulates gastrointestinal motility, visceral sensation and enteric neuronal function in the mouse. The effects of AA‐5‐HT on visceral sensation, enteric neuronal function and colonic motility are differentially mediated by CB1, TRPV1 and non‐CB1/TRPV1 mechanisms.